İç Mimaride Loft Tasarımı - Erdemir, Zuhal (The Turkish Online Journal of Design Art and Communication, 2015)
Loft concept is indicated as “Loft, attic" or "on the top floor, so the floor immediately below the roof. Initially, while the roof or the floor immediately below the roof meaning, "warehouse, commercial building" has been added also. Loft is converted back to the housing of the old factory building or warehouse space by the time. Firstly, Loft spaces are preferred by artists such as painters and sculptors have been used as a residence and studio. In this way, they meets the needs of both work and living areas as well. The most important reason to choose Loft spaces by Artists is the solution for the problem of homelessness that it allows the use of both different and cheap. Heating or plumbing is such as being open hardware or walls often have a style that did not originate from the bare concrete or masonry, it is a temporary situation created by the cheap housing.
Keywords: Loft; Dönüşüm; Loft Mekânları; Çatı Katı; Açıklık; Loft Yaşamı; Conversion; Lofts Space; Attic; Opening; Loft Living